The impact of insurance type on listing status and wait‐list mortality of patients with left ventricular assist devices as bridge to transplantation - Alexandros Briasoulis; Emmanuel Akintoye; Chakradhari Inampudi; Aziz Hammoud; Paulino Alvarez (ESC Heart Failure, 2020)
Abstract Aims Adequate health insurance coverage is necessary for heart transplantation (HT) candidates. Prior studies have suggested inferior outcomes post HT with public health insurance. We sought to evaluate the effects of insurance type on transplantation rates, listing status and mortality prior to HT. Methods and results Patients ≥18 years old with a left ventricular assist device implanted and listed with 1A status were identified in the United Network for Organ Sharing registry between January 2010 and December 2017, with follow‐up through March 2018. Patients were grouped based on the type of insurance private/self‐pay (PV), Medicare (MC), and Medicaid (MA) at the time of listing. We conducted multivariable competing risks regression analysis on listing status and mortality on the waiting list, stratified by insurance type at the time of listing. We identified 2604 patients listed in status 1A (PV: 51.4%, MC: 32.1%, and MA: 16.5%). MA patients were younger (43.5 vs. 56.4 for MC vs. 51.5 for PV, P < 0.001) and less frequently White (P < 0.001). The cumulative incidence of HT did not differ among the three insurance types (PV: 74.8%, MC 76.3%, and MA 71.1%, P = 0.14). The cumulative mortality on the waiting list prior to HT was not different among groups (PV: 29.3%, MC 26.3%, and MA 21.8%, P = 0.94). Μore patients with MA were removed from the list because of improvement of their condition (MA 40.3% vs. MC 28.3% and PV 32.8%). Conclusions We did not detect any disparities in listing status and mortality among different insurance types.